SHRIMP U-Pb age constraints on magmatism and high-grade metamorphism in the Salem Block, southern India - Clark, Chris; Collins, Alan; Timms, Nicholas Eric; Kinny, Peter; Chetty, T.; Santosh, M. (Elsevier Science BV, 2009)
In this paper, we present Sensitive High Resolution Ion Microprobe (SHRIMP) U and Pb isotope analyses of zircon from a charnockite and a charnockite-hosted leucosome in order to determine the age of magmatism and anatexis related to high-grade metamorphism immediately to the north of the Palghat Cauvery Shear System (PCSS), a proposed Neoproterozoic terrane boundary within Southern India. Weakly luminescent, oscillatory-zoned cores in I06-128 and analyses with high Th/U ratios in I06-129 yield weighted mean 207Pb-206Pb ages of 2538 6 Ma and 2529 7 Ma. These two ages are statistically indistinguishable and are interpreted to reflect the crystallisation age of the original magmatic protolith to the charnockite. Low Th, Th/U ratio and brightly luminescent overgrowths and complete zircon grains in I06-128 and I06-129 give weighted mean 207Pb-206Pb ages of 2473 8 Ma and 2482 15 Ma respectively.The two ages are statistically distinct and are interpreted to constrain the timing of post-crystallisation high-grade metamorphism and partial melting of the magmatic rocks that crystallised at ~2530 Ma. The new ages of the charnockites are consistent with the suggestion that this activity is related to accretionary processes on the margin of the Dharwar craton and may be related to a second stage of convergent tectonics and collision on the margin of Kenorland. There is no evidence of a pervasive Neoproterozoic high-grade metamorphic event associated with the amalgamation of Gondwana recorded in these rocks. However, the possibility that deformation waslocalised along discrete shear zones at this time cannot be discounted. The data from this study add weight to the hypothesis that the PCSS represents a Neoproterozoic suture zone along which the Dharwar Craton and the microcontinent Azania, with its constituent Madurai and Trivandrum Blocks in the Southern Granulite terrane, collided at ca. 530 Ma Ga during the closure of the Mozambique ocean.